Prepoznavanje emocionalnog izraza lica kod srednjoškolaca različitih intelektualnih sposobnosti - Medić-Ivanovski, Miroslava; Lalatović, Staša; Krstić, Nadežda (Specijalna edukacija i rehabilitacija, 2025)
Introduction. Despite a growing interest in social cognition, the evidence on emotion recognition ability is still inconsistent, partly due to the complexity of related constructs as well as methodological inconsistencies. Objectives. To test the discriminability of a robust technique of facial emotion recognition (ER), including only one task per emotion in a group of adolescents of diverse general ability, analyze the relationship between ER and basic intelligence indicators, and explore assumed gender differences in ER. Method. A group of 199 secondary school students, 95 enrolled at a regular schooling system (typically developing group, TD) and 104 at a special school for the education of students with intellectual disability (44 of borderline intellectual abilities and 60 with mild intellectual disability; respectively BIA and MID group) was given a task to (forcedly) recognize displays of eight different emotions (six basic and two control) on photographs of the same male showing emphasized facial expression. Results. The reliability of the technique is α = .68. The TD group achieved better scores on the ER task (M = 5.35, SD = 1.98) compared to students from the special school (M = 3.67, SD = 1.81), t(197) = 6.24, p < .001, d = 0.89, and when all three groups were separately compared (F(2, 196) = 23.06, p < .001, η2 = .19). A significant correlation of the ER task score with IQm (r = .32, p = .01) and IQt (r = .39, p = .002) was found only in the BIA group. The ER task did not detect differences in ER related to gender, except in recognizing sadness in the TD and BIA groups. Conclusion. The applied procedure is discriminative in testing the ability to recognize basic facial emotions. The obtained differences are related to IQ at the level of groups formed according to the general ability to a small extent.